Edna Manley Art / Sculptures and Drawing 1922 - 1970 - Morrison, k (Kingston, Jamaica K. Morrison, 1960)
This is a photograph done by K. Morrison of one Edna Manley's Sculptures and drawings 1922 -76. This piece is titled "the Land" c. 1960. The artwork /sculpture is the form of a naked upper female body. One of her arms is between her breasts. A female is pleasant, almost smiling, she has long braided hair.
Edna Manley's Sculptures and Drawings 1922 - 76
Available on Special Collection Floor
Keywords: Edna Manley; Edna Manley; Art